The use of effect biomarkers in human biomonitoring studies: exposure to hexavalent chromium - Gomes, Bruno Costa (2020)
Hexavalent chromium, Cr(VI) is a human carcinogen (Group 1, IARC), and its expo-sure has been associated with increased lung cancer risk, particularly in exposed workers. The general population may be exposed to Cr(VI) through food, drinking water and tobacco smoke. Under the Human Biomonitoring for Europe Initiative (HBM4EU), Cr(VI) has been considered a priority substance, indicating the need for generating and analyzing data on human exposure and effects, both as single sub-stance and in mixtures. Although many epidemiological studies have reported data on human exposure to Cr(VI), comparably fewer included effect biomarkers assess-ment. However, these biomarkers are central to identify early biological effects be-fore the onset of any adverse health effect. Additionally, biomarkers provide a link between human exposure and health outcomes, when considered in an adverse outcome pathway (AOP) perspective. In this work, we present the results of a critical review on the conventional and po-tentially new biomarkers for Cr(VI) early biological effects, which may be linked to adverse health outcomes in humans. The results show that the most frequently analyzed effect biomarkers concerning Cr(VI) exposure have been those associated with oxidative stress and genotoxicity (comet and micronucleus in blood cells). Urinary 8-isoprostane, a marker of lipid pe-roxidation, has also been used to relate Cr(VI) exposure to lung cancer. More recent-ly, single-gene alterations as well as omics-based biomarkers e.g., genomic or epigenomic changes and protein signatures, have been pointed as novel effect bi-omarkers, but they still need to be further developed and validated. In the literature revision, the most important knowledge gaps have also been identi-fied and discussed, such as the need of additional mechanistic data, in the perspec-tive of building an AOP for Cr(VI) occupational exposure and lung cancer